Construction noise annoyance among the public residents - Darus, Nadirah (Penerbit UTM Press, 2015)
Construction activities generate construction noise may cause noise annoyance among the public residents. The aim of this study is to investigate the noise annoyance level due to the sound pressure levels and the distances from the construction sites. Three public resident areas around Johor which located near to the construction sites have been selected. Two important indicators such as sound pressure levels and distances between the receiver and the noise sources were measured. 42 questionnaires were randomly distributed to the public residents who live near to the construction sites. The results showed that all respondent have different annoyance levels due to the construction noise. The sound pressure levels received by the public residents are increasing with the decreasing of the distance between the receiver and the noise sources. Thus, the relationship of noise annoyance levels is directly proportional to the sound pressure levels produced from construction sites. Meanwhile, the noise annoyance levels are decreasing with the increasing of the distances. As a conclusion, the public residents who live nearer to the construction sites suffered from a high noise annoyance level as expected.